Students' Attitudes toward Using Literary Works in Learning English in EFL Context - Muhammad Rifqi; Januarius Mujiyanto; Rudi Hartono; Sri Wuli Fitriati (Universitas Negeri Semarang, 2022)
Literary texts in learning English have been used worldwide in teaching English in various contexts, i.e., first, second, and foreign languages. However, debates among educators about its effectiveness continuously occur. In this research, we tried to examine the students' attitudes toward using literary works for teaching English. Apart from studies about using literary texts in English teaching, this research was done with a combination of imaginative recreation. The research subjects were the 3rd-semester students taking the